Present State of Coffee Production and Consumers Behaviour on Preferences of Nepalese Coffee - Karki, Yogendra Kumar; Karki, Punya Prasad (Journal of Management and Development Studies, 2016)
Nepal has enormous potential for cultivation of coffee as the climate is suitable throughout the mid hills of the country. High demand of coffee and higher price, comparative to other crops in the international market lure farmers for its cultivation. This paper deals with the present state of same product focusing on the production and consumer behaviour on preferences of Nepalese coffee. For the study, growth rate in area, production and yield of coffee was estimated using the secondary information. Similarly import and export trend of coffee was estimated through secondary information. Consumers behaviour on preferences of coffee was analyzed through individual survey by selecting 120 consumers randomly including coffee-drinker and restaurant owners. Semi-structured questionnaire was administered to study the consumers behaviours. The study revealed that annual growth rate of area under coffee and its production during 1999 to 2013 was 11.61 percent and 10.59 percent, respectively. Whereas, the productivity of coffee during the same period decreased by 1.01 percent. The decline in productivity might be due to problem of irrigation, inadequate nutrient supply and diseases and pests. Large proportion of coffee produced in Nepal is exported. However, the analysis showed that there is decrease of coffee export by 25.6 per cent annually due to increase in local consumption of coffee. Analysis also showed that the foreign people prefer foreign coffee in comparison to Nepalese coffee (p-value is